Cambridge checkpoint mathematics teacher's resource 7 - Jones, Mary.; Fellowes-Freeman, Diane; Sang, David (Cambridge : Cambridge University Press, 2012)
Cambridge checkpoint science 7 matches the requirements of stage 7 of the revised Cambridge Secondary 1 curiculum framework. This cd-rom contains answers to questions from the coursebook, answers to exercise from the workbook, teaching ideas, notes on practical activities, worksheets and animations to illustrate key concepts.
'Endorsed by University of Cambridge International Examinations'--container cover.Title from container.
CD-ROM for Windows XP/Vista and Mac OSX 10.4 or higher.
Keywords: Science -- Study and teaching